2009
DOI: 10.1007/s12291-009-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of liver and kidney function are influenced by thyroid function-a case-controlled follow up study in Indian hypothyroid subjects

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 18 publications
3
28
1
Order By: Relevance
“…Unfortunately, the various symptoms caused by the resultant hypothyroidism may cause patients to be reluctant to undergo the following RIT. These biochemical changes in uncomplicated hypothyroidism are usually mild and reversible with adequate thyroid hormone therapy [13,14]. This alternative RIT method is based on rhTSH administration and allows the patient to maintain a euthyroid level of fT4 during RIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the various symptoms caused by the resultant hypothyroidism may cause patients to be reluctant to undergo the following RIT. These biochemical changes in uncomplicated hypothyroidism are usually mild and reversible with adequate thyroid hormone therapy [13,14]. This alternative RIT method is based on rhTSH administration and allows the patient to maintain a euthyroid level of fT4 during RIT.…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatinine (Cr) levels increase in the uncomplicated hypothyroid state before RIT in patients with normal renal function because of a decrease in renal blood flow and glomerular filtration [7,11]. Recent studies have also shown that liver function also undergoes a reversible change before RIT and recovers to the euthyroid state after thyroid hormone replacement [13][14][15]. Recent studies have also shown that liver function also undergoes a reversible change before RIT and recovers to the euthyroid state after thyroid hormone replacement [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid is an important endocrine gland and produces two main hormones thyroxine (T4) and tri-iodo thyronine (T3) [7][9]. Both of these hormones are under control of thyroid stimulating hormone (TSH) released by anterior pituitary gland and in turn it is controlled by thyrotrophin releasing hormone (TRH) of hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothyroidism has been associated in a few case reports with cholestatic jaundice attributed to reduced bilirubin and bile excretion [13]. In experimental hypothyroidism, the activity of bilirubin UDP glucuronyltransferase is decreased, resulting in a reduction in bilirubin excretion [14]. Thyroid hormones (THs) also oppose the action of insulin and stimulate hepatic gluconeogenesis and glycogenolysis; they up-regulate the expression of genes such as glucose transporter type-4 (GLUT--4) and phosphoglycerate kinase, involved in glucose transport and glycolysis, respectively, thus acting synergistically with insulin facilitating glucose disposal and utilization in peripheral tissues [15].…”
Section: Introductionmentioning
confidence: 99%